Do sustainability or environmental, social and governance (ESG) practices influence emerging Asia banks performance during COVID-19 pandemic? / Mustapa Abdullah ... [et al.] - Abdullah, Mustapa; Hassan, Hasroleffendy; Hassan, Hamizah; Jamalurus, Hasmah Laili (Research Management Centre (RMC), 2023)
As the COVID-19 crisis unfolds, the banking industry has once again come under scrutiny, particularly due to the recent collapses of notable financial institutions in the United States and Switzerland. This warrants an urgent reassessment of regulations, financial governance, and risk management practices. This research aims to investigate the relationship between Environmental, Social, and Governance (ESG) practices and bank performance within emerging Asian economies. Its urgency is underpinned by these recent financial disruptions and the need for resilient banking systems geared for sustainability. By exploring bankspecific performance indicators like the Net Interest Margin (NIM) and Capital Adequacy Ratio (CAR), this study offers an approach differentiated from traditional profitability measures, namely Return on Assets (ROA), Return on Equity (ROE), and Tobin's Q. This paper's quantitative approach includes multivariate regression analysis of unbalanced panel data from all publicly listed banks in these economies between 2018 and 2022. This research not only provides reflections on these institutions' performance during a global crisis but also illustrates the imperative for ESG assimilation in bank strategy and operations as a safeguard against future uncertainties.